Agriculture, Water, and Land Policies to Scale Up Sustainable Agrifood Systems in Georgia : Synthesis Report and Way Forward - World Bank (Washington, DC: World Bank, 2022)
This Synthesis report summarizes the main constraints and opportunities that Georgia faces in amplifying the contribution of the agriculture sector to the country’s economic growth and diversification, employment creation, poverty reduction, food security and nutrition, and climate resilience and mitigation. Successful achievement of these multiple objectives, however, requires an integrated set of multi-sectoral policies. Synergistic public and private investments in agriculture, water, and land can lead to increased production and productivity by transitioning from low returns from agriculture to high-value crop production.